Análise das tecnologias via rádio e fibra óptica na comunidade quilombola de Umarizal-Baião - MEIRELES, Assis dos Santos (2023)
This work discusses radio and fiber optic technologies in the quilombola community of Umarizal. The research addresses the two technologies present in the Conect_A&D internet provider in the community. Thus, the general objective was to analyze the radio and fiber optic technologies that are in operation at the internet provider in the quilombola community of Umarizal, Baião. This research aimed to obtain comparative data between the two technologies, in this sense, the field study methodology was used with a qualitative approach. For this, specific applications and software were used, among other practical analyzes in order to achieve the general objective of the research. The results obtained reveal the differences between the technologies in terms of speed, stability, costs, advantages and disadvantages. Finally, the results indicate that despite the high cost being twice as high to implement fiber optic technology, it offers a better quality service and higher bandwidths. However, in the community of Umarizal, the radio route stands out for its ability to serve users where there are no conditions to lay optical cables.